Effectiveness of Motor Skills Development in 5th-7th Grade Girls at Different Modes of Physical Exercises - Olga Ivashchenko; Tamila Abdulkhalikova; Miroslava Cieślicka (OVS LLC, 2017)
The objective is to determine the influence of the physical exercises modes on effectiveness of motor skills development in 5th-7th grade girls.  Materials and methods. The study involved 5th grade girls (n = 28), 6th grade girls (n = 28) and 7th grade girls (n = 24). To solve the tasks set, the study relied on general scientific and special research methods, methods of mathematical experiment-planning. Studying the influence of different variants of the educational process structure, namely: the number of repetitions (x1) and the rest intervals (x2) on acquisition of the technique of physical exercises performance, provided for achieving the objective. A full 22 type factorial experiment was conducted. The 5th-7th graders were divided into training groups according to the experiment plan. In total, there were twelve experimental groups organized, four in each class. Results. The analysis of the regression equations shows that the rest interval between repetitions (x2) has the greatest influence on teaching 5th-7th grade girls physical exercises, with the number of repetitions (x1) being of somewhat less significant influence. The relation between these factors (x1x2) has a considerable weight in teaching to "rope climb in two or three sets" and to do a "pullover mount with a swing of one and a push-off with the other leg". Conclusions. To increase the effectiveness of teaching 5th-7th grade girls physical exercises, the number of repetitions in throwing exercises should be increased to twelve times, and the rest interval reduced to 60 seconds. In the 7th grade, the number of repetitions should be reduced to six times, and the rest interval - to 60 seconds. The rest intervals in the exercises: "pullover mount with a swing of one and a push-off with the other leg" and "rope climbing in two or three sets", should be reduced to 60 seconds and the number of repetitions - to six.